Innovation, Ethics, and Entrepreneurship - Miles, Morgan P. (Journal of business ethics, 2004)
This paper is a response to Ray's (2004) recent proposal that the intellectual property rights (IPR) attached to potentially life saving/life sustaining innovations should become public goods in cases where markets are either unable or unwilling to pay for the creation of the intellectual property. Using a free market approach to innovation based on Western moral philosophy, we suggest that treating intellectually protected life saving/life sustaining innovations as public goods will likely reduce social welfare over the long term.